Effect of Melatonin on Delirium After on-Pump Coronary Artery Bypass Graft Surgery: A Randomized Clinical Trial - Javaherforoosh Zadeh, Fatemeh (Iran J Med Sci, 2021)
BACKGROUND: Patients undergoing cardiac surgery are particularly prone to delirium. This study aimed to evaluate the effect of melatonin administration on the inhibition of postoperative delirium in patients undergoing open-heart surgery. METHODS: This study was conducted as a double-blind randomized clinical trial in Golestan Hospital. Ahvaz, Iran, (September 2018 to March 2019). Sixty patients undergoing elective on-pump coronary artery bypass graft surgery were enrolled in the study, and they were randomly divided into a group receiving 3 mg of melatonin and a group receiving a placebo. The main outcomes were delirium occurrence and delirium intensity up to 48 hours after extubation. The data were analyzed using SPSS, version 22, (SPSS, Chicago, IL). Group comparisons were performed using the t test and the Chi-square test. Statistical significance was defined as a P value of less than 0.05. RESULTS: On the first postoperative day, delirium developed in four (13.3%) patients in the melatonin group and 11 (36.6%) patients in the control group; the difference between the groups was statistically significant (P=0.037). On the second postoperative day, delirium developed in three (10%) patients in the melatonin group and 14 (46.6%) patients in the control group, with the difference in the incidence of delirium between the groups constituting statistical significance (P=0.029). The severity of delirium between group was significant on the first and second postoperative days (P=0.003). CONCLUSION: Melatonin may be effective in reducing the severity of delirium after cardiac surgery. The effect of melatonin as a delirium prevention agent should be considered in patients admitted in the cardiovascular intensive care. Trial Registration Number IRCT20180909040979N3.